Computational Investigate Into The Anti-breast Cancer Potential of Panax Ginseng Via Ubiquitin-Specific Protease 46 Inhibition. - Khanh Huyen Thi Pham , Khanh Huyen Thi Pham; Nguyễn, Tấn Khanh (Tạp chí Khoa học Đại học Đông Á, 2025)
Breast cancer is a disease with a high mortality rate in women worldwide. The rate is increasing, escalating the medical burden in developed countries as well as developing countries. Several risk factors contribute to the development of this disease, including early puberty, late menopause, postmenopausal obesity, and the use of oral contraceptives or hormone replacement therapy, all of which slightly increase the risk of breast cancer. The search for new treatments to reach the majority of patients is very necessary. Notably, by searching for the pathogenesis, many studies have shown that Ubiquitin-Specific Protease 46 is involved in the development and metastasis of breast cancer cells. This insight has prompted efforts to identify potential inhibitors with biological activity capable of targeting this enzyme. Our study has identified Aposiopolamine, a compound derived from Panax ginseng, which demonstrates strong inhibitory potential against Ubiquitin-Specific Protease 46 and exhibits favorable pharmacokinetic properties.